ANALISIS KEBERLANJUTAN SOSIAL UMKM KOPI BUBUK PEREMPUAN WIRAUSAHA DI SUMATERA BARAT - Ninda Novita; Burhanuddin; Rachmat Pambudy (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2025)
Agroindustry-based MSMEs are a